KAJIAN PEMBUATAN NUGGET DARI JANTUNG PISANG DAN TEPUNG KEDELAI DENGAN PENAMBAHAN IKAN GABUS (Opiocephalus striatus) - Simbolon, Monica Valentina Therescova; Pato, Usman; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this research was to obtain the formulation of the banana heart and soybean flour best to obtain nuggets which the meet the quality of Indonesian National Standard (SNI) No. 01-6638-2002. This study was conducted experimentally using completely random design with 4 treatments and 4 replicates. The ratio between the banana, soybean flour and common snakehead fish treatment were JK1 (40:30:30), JK2 (45:25:25), JK3 (50:20:30) and JK4 (55:15:30). Chemical analysis show that the water content ranged from 48,84% to 52,05%, the protein 11,56%-14,52%, fat 22,43%-22,55%, fiber content 5,46%-6,07%, ash content of 1,89-2,01 levels and carbohydrate content of 10,54%-11,96%. Results of cluster analysis (AHC) on hedonic test and PCA analysis on descriptive test then analyzed using prefference mapping to determine the level of acceptance and satisfaction of panelists. The best treatment that gives the impression of acceptance and satisfaction of the most high was JK3 which ranged from 90% to descriptive characteristics nugget dominant was flavorful banana, taste of banana, taste of common snakehead and compact texture. So the results of the research show that the best treatment was JK3 (50 banana: 20 soy flour: 30 common snakehead fish) which the meet the quality of Indonesian National Standard (SNI) No. 01-6638-2002 and gives most high acceptance of panelists, ranged 90%. Keywords: Nugget, banana’s heart, soybean meal, AHC, PCA, preference mapping.